Assessing the response of Nigeria's capital market to the Covid-19 pandemic - Peter Adekunle; Udochukwu Nwachukwu; Oloyede Betsy (West African Journal of Monetary and Economic Integration, 2021)
This paper assessed the response of Nigeria's capital market to the COVID-19 pandemic using daily observations from the 28th of February 2020 to the 26th of June 2020. The study also examined whether the pandemic had different effects on the different sectors of the capital market in Nigeria. It employed the autoregressive distributed lag (ARDL) model bounds testing technique to estimate the different models specified and analyze the output. The findings showed that the COVID-19 pandemic has adversely affected the activities of the Nigerian capital market especially with respect to the NSE all share index. Specifically, the study reveals that the COVID-19 pandemic has adversely affected some sectors of the capital market in the short-run. However, the market performance will improve in the long run should the standard measures put in place to overcome Covid-19 pandemic are upheld. It is important that investors and government responses to the COVID-19 pandemic should take cognizance of the observed heterogeneities in the response of the capital market to the pandemic. This will guide investors' preferences and government's policies in that regard.
Keywords: C22; I15; 330; COVID-19 pandemic; Capital market; Sectoral stocks; ARDL model